Digital Transformation and Branding for Empowering the Creative Economy Based on Local Wisdom: Transformasi Digital dan Branding untuk Pemberdayaan Ekonomi Kreatif Berbasis Kearifan Lokal - Yusup, Muhamad; Ariq, Muhammad Faris; Nasution, Erni Juliana Al Hasanah; Fahreza, Aulianda Zahrina; Edwards, John (ADI Bisnis Digital Interdisiplin Jurnal, 2025)
Digital transformation and strengthening local brand identity are key to encouraging creative economic empowerment based on local wisdom. This study aims to analyze the influence of creative communication strategies, brand personality, digital marketing engagement, user-generated content, and social media platform interactivity on the effectiveness of village community empowerment programs. Using a quantitative approach and Structural Equation Modelling (SEM) methods through SmartPLS software, data were collected from 300 respondents involved in a local potential-based digital entrepreneurship program. The results show that creative communication strategies and interactive social media platforms significantly increase digital participation and community emotional connection to local products. Brand personality and user-generated content also contribute positively to creative business image and market appeal. This study emphasizes the importance of integrating local values into digital branding narratives to create differentiation and consumer loyalty. These findings provide practical implications for stakeholders in designing empowerment policies and programs that are technology based yet rooted in local culture. Thus, this study contributes to the development of a sustainable and inclusive village creative economy ecosystem in the digital era.